If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-96=-8(5-x)
We move all terms to the left:
-96-(-8(5-x))=0
We add all the numbers together, and all the variables
-(-8(-1x+5))-96=0
We calculate terms in parentheses: -(-8(-1x+5)), so:We get rid of parentheses
-8(-1x+5)
We multiply parentheses
8x-40
Back to the equation:
-(8x-40)
-8x+40-96=0
We add all the numbers together, and all the variables
-8x-56=0
We move all terms containing x to the left, all other terms to the right
-8x=56
x=56/-8
x=-7
| -6p-14=2-4p | | -2(.25s)-5+3=3 | | 0.2(30x-10)=15 | | 4(z-8)-6=10 | | 2x+(-3x-10)=-154 | | -2-7n=-8n+8-4 | | 6=a+2a | | 2(1+7x)-1=-27+7x | | -18=3x=6 | | 180=-4(-3+7m) | | 9(z-3)=122 | | 7y-8y-9=10 | | -4(8)-5n=13 | | 3x-5(x+8)=-16-5x | | 6y/5+3/5=0 | | 36000+2000x=30000+2400x | | (1/3)*b=25 | | 3p-1=4p | | (1/3)b=25 | | 18x=7/6 | | 23-17k-1=-2k+367 | | 11=1+6v+4v | | N+3+2n=18 | | 4(5n+7)-3n=12n-27 | | 2x+9/8=14 | | 5x-4x=-2+7 | | 12-6/2x3=11 | | -90+x=53-12x | | 12-3n=10-2n | | 6n-2n=-24 | | 4x^+2x=0 | | 4x−9+19=8x−14 |